Antioxidant Activity of Ethanol Extract Combinations of Jeruk Purut Leaf (Citrus hystrix Dc.) and Jati Belanda Leaf (Guazuma ulmifolia L.) - Arina Nisyya Nadhira; Safira Maharani; Fransisda Aulia Zatsyia; Ika Trisharyanti; Dian Kusumowati (Journal of Tropical Pharmacy and Chemistry, 2018)
Ethanol extracts of Guazuma ulmifolia L. and Citrus hystrix Dc., have a strong antioxidant activity. The purpose of this research is to determine the antioxidant activity of ethanol extracts combination of Guazuma ulmifolia L. (jati belanda leaf) and Citrus hystrix Dc (jeruk purut leaf). Determination of antioxidant activity was done by DPPH method (1,1-diphenyl-2picrylhydrazil) using UV-Vis spectrophotometer with maximum wavelength 516.5 nm. The antioxidant activity of jeruk purut leaf is smaller than jati belanda leaf (IC50 48.70 mg/mL for jeruk purut leaf, IC50 35.92 mg/mL for jati belanda leaf). Antioxidant activity of the two extracts combination was lower than the antioxidants of each extract (without combination). The low antioxidant activity of both extract combination due to the antagonist activity as the interaction of the content of each extract so that the extract combination showing a weaker antioxidant activity. At the concentration of each different comparison of each extract combination volume shown no difference with P-value > 0.05 (P-value: 0.99).